2017
DOI: 10.1007/s00299-017-2149-5
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide analysis of autophagy-related genes in banana highlights MaATG8s in cell death and autophagy in immune response to Fusarium wilt

Abstract: MaATG8s play important roles in hypersensitive-like cell death and immune response, and autophagy is essential for disease resistance against Foc in banana. Autophagy is responsible for the degradation of damaged cytoplasmic constituents in the lysosomes or vacuoles. Although the effects of autophagy have been extensively revealed in model plants, the possible roles of autophagy-related gene in banana remain unknown. In this study, 32 MaATGs were identified in the draft genome, and the profiles of several MaAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 73 publications
4
46
0
1
Order By: Relevance
“…Similarly, a total of 19 core CsATGs, including 35 members, were identified from the sweet orange genome in this study. The quantity of ATGs in sweet orange is similar to the quantity in grape (35 VvATGs) [13], banana (32 MaATGs) [12], rice (33 OsATGs) [7], and foxtail millet (37 SiATGs) [11], suggesting very conservative evolution of ATGs in these plants. Among the 19 core CsATGs, we found that CsATG1, CsATG8, and CsATG18 contained multiple members, which is similar to that in Arabidopsis and other plants [1,8,13].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Similarly, a total of 19 core CsATGs, including 35 members, were identified from the sweet orange genome in this study. The quantity of ATGs in sweet orange is similar to the quantity in grape (35 VvATGs) [13], banana (32 MaATGs) [12], rice (33 OsATGs) [7], and foxtail millet (37 SiATGs) [11], suggesting very conservative evolution of ATGs in these plants. Among the 19 core CsATGs, we found that CsATG1, CsATG8, and CsATG18 contained multiple members, which is similar to that in Arabidopsis and other plants [1,8,13].…”
Section: Discussionmentioning
confidence: 72%
“…Most ATGs were first identified and functionally characterized by mutagenesis studies in yeast [2]. More than 30 ATGs have now been identified in yeast, and 23, including ATG1-10, [12][13][14][16][17][18]20,27,29,31,TOR,VPS15,and VPS34, are considered to be the core ATGs participating in autophagy [3,4]. In Arabidopsis, around 40 homologues to these core ATGs have been identified, except for ATG14, 17,27,29, and 31 with no homologues [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The endogenous SA level in plant leaves was extracted and examined as described previously by Shi et al (2014) and Wei et al (2017b).…”
Section: Quantification Of Endogenous Sa Levelmentioning
confidence: 99%